Imaging tests for the diagnosis of COVID-19 - McInnes, Matthew D.F.; Leeflang, Mariska M.G.; Salameh, Jean Paul; McGrath, Trevor A.; van der Pol, Christian B.; Frank, Robert A.; Prager, Ross; Hare, Samanjit S.; Dennie, Carole; Spijker, René; Deeks, Jonathan J.; Dinnes, Jacqueline; et al. (John Wiley & Sons Inc., 2020)
Objectives: This is a protocol for a Cochrane Review (diagnostic). The objectives are as follows:. The primary objective is to determine the diagnostic accuracy of chest imaging (computed tomography (CT), chest X-ray and ultrasound) in the evaluation of people suspected to have COVID-19. This may also refer to specific signs, such as a particular CT finding. Secondary objectives To evaluate whether these imaging tests are sufficiently accurate to rule out COVID-19 (main measure of interest will be the negative predictive value) To evaluate the rate of positive imaging in patients with initial RT-PCR negative results who have a positive result on a follow-up RT-PCR test To determine if there is an association between number of days after symptom onset, symptom severity and the findings on chest imaging for patients with COVID-19 To determine the rate of discrepancy or agreement between CT, chest X-ray and ultrasound findings To evaluate for ‘threshold’ effects of imaging findings of COVID-19 and accuracy measures To determine the rate of alternative diagnoses identified by chest imaging.
Keywords: Taverne; Pharmacology (medical)